Assessment of pediatric employees' and residents' degree of knowledge on the 9th step of a Baby-Friendly Hospital in Teaching Maternity in Aracaju/SE (Research, Society and Development, 2021)
Introduction: The use of teats, pacifiers and bottles, when not used to stimulate the baby's suction maturation, contributes to early weaning. Objective: To assess the degree of knowledge of pediatric employees and residents in a teaching maternity hospital on the 9th step of the "Ten Steps to Successful Breastfeeding". Methodology: Cross-sectional, prospective, descriptive research. The study universe consisted of 51 professionals from the Intermediate Unit of Neonatal Care of a Teaching Maternity in Aracaju/SE. Data collection was obtained through a questionnaire, validated by WHO, from the Baby-Friendly Hospital Initiative, specifically the ninth step which refers to the non-use of pacifiers. Results: The 9th Step has been observed to be known by 60.4% of professionals. There is no relationship between the fact that the employee is a mother and the variables related to the use and knowledge of the ninth step. Regarding the offer of some oral habit instruments, 64.0% of the participants stated they do, while 57.1% claimed that the habit instrument interferes with breastfeeding training. The aim of using a pacifier, according to 70% of the professionals, is to soothe the baby. In addition, 81.6% stated that the habit of offering pacifiers already existed or arose with the impossibility of permanent monitoring of the mother due to the new Coronavirus pandemic. Conclusion: In conclusion, the collaborators are aware of Step 9 however, this awareness is not represented in practice.